Fragmentary myoclonus in idiopathic rapid eye movement sleep behaviour disorder. (24th January 2019) - Nepozitek, Jiri; Dostalova, Simona; Kemlink, David; Friedrich, Latica; Prihodova, Iva; Ibarburu Lorenzo y Losada, Veronika; Dusek, Petr; Bezdicek, Ondrej; Nikolai, Tomas; Perinova, Pavla; Dall'Antonia, Irene; Dusek, Pavel; et al.
Summary : Fragmentary myoclonus is a result of muscle activity consisting of brief potentials in surface electromyography during polysomnography. Excessive fragmentary myoclonus is defined by increased intensity of the potentials. A few studies report excessive fragmentary myoclonus occurrence in neurodegenerative diseases. Because idiopathic rapid eye movement sleep behaviour disorder is considered as an early stage of neurodegeneration with involvement of the brainstem, we charted the prevalence and quantified the intensity of excessive fragmentary myoclonus in idiopathic rapid eye movement sleep behaviour disorder. Twenty‐nine patients (one woman, 28 men, mean age 68 years, SD 6.2) and 29 controls (two women, 27 men, mean age 65.6 years, SD 8.6) underwent polysomnography. Fragmentary myoclonus potentials were identified and counted according to internationally used criteria. Fragmentary myoclonus intensity was quantified by the fragmentary myoclonus index. Excessive fragmentary myoclonus was diagnosed in 75.9% (22 subjects) in idiopathic rapid eye movement sleep behaviour disorder, while in 34.5% (10 subjects) among the controls ( p = 0.003). Quantitative analysis showed a wide‐range fragmentary myoclonus index in idiopathic rapid eye movement sleep behaviour disorder (4.0–632.4; median 60.7) and in the controls (0.8–938.1; median 34.3). The overall difference in fragmentary myoclonus index was not significant between the groups; however, patients with idiopathic rapid eye movement sleep behaviour disorder showed trends for higher fragmentary myoclonus index scores in wakefulness ( p = 0.027), N1 ( p = 0.032), N3 ( p = 0.046) and R ( p = 0.007). Fragmentary myoclonus index does not correlate with age, idiopathic rapid eye movement sleep behaviour disorder duration or R stage atonia deficiency. The prevalence of excessive fragmentary myoclonus is higher in idiopathic rapid eye movement sleep behaviour disorder compared with the controls, so fragmentary myoclonus should be taken into account in future research of rapid eye movement sleep behaviour disorder and motor control in sleep.